ANALISIS PENINGKATAN KUALITAS GEOMETRI DENGAN MENGGUNAKAN TITIK IKAT BUNDLE ADJUSTMENT (STUDI KASUS DATA PLEIADES WILAYAH KABUPATEN MADIUN DAN KABUPATEN MAGETAN) - Sari, Inggit Lolita; Brahmantara, Randy Prima (Institut Teknologi Sepuluh Nopember, 2019)
Recently, the utilization of very high spatial resolution data such as Pleaides has reached at a high demand. Particularly to support disaster mitigation, where automation and fast image processing are necessary and unavoidable. Pleiades imagery has been acquired at LAPAN ground station starting in 2018. This study examines the improvement of the Pleiades images geometry accuracy processed using the bundle adjustment (BA) method in order to support image mosaicking where case study is located in the Madiun regency and the Magetan regency. This method uses parameters to relate the geometry between scenes by using tie points. These points are located in the intersection area between scenes. Geometry quality assessment of the imagery produced using BA correction are measured by comparing between the coordinate of the imagery and the coordinates obtained from the field measurement. The assessment shows that BA geometry correction has improved the geometry quality of the images which nearly similar to the field measurement and achieved a better geometry accuracy compare to the images processed without BA method.